Prior knowledge, older age, and higher allowance are risk factors for self-medication with antibiotics among university students in southern China. - Hui Pan (Public Library of Science (PLoS), 2012)
Background Self-medication with antibiotics (SMA) has been reported among university students in many countries, but little research has been done on this issue in China. The objective of this study was to evaluate knowledge and behaviors of university students and risk factors concerning SMA. Methodology/principal findings Using a novel questionnaire-based data collection instrument, an anonymous online survey was conducted with the students of Shantou University (STU), a university comprising 8 schools/colleges in eastern Guangdong, China. Of 1,300 respondents (13.8% of total eligible participants), 47.8% had self-treated with antibiotics. Logistic regression analysis identified prior knowledge of antibiotics (PKA), older age, and higher monthly allowance as independent risk factors for SMA. PKA significantly influenced students' knowledge about antibiotics, their uses, and common adverse reactions (all p<0.05). Among self-medicated students, 61.7% used antibiotics at least twice in the previous year. Community pharmacies were the major source of self-prescribed antibiotics. Reported common indications for SMA were sore throat (59.7%), fever (38.2%), cough (37.4%), runny nose (29.3%), and nasal congestion (28.7%). While 74.1% of self-medication episodes were based on students' own experiences, only 31.1% of students claimed to understand the package insert. Alteration of antibiotics and dosage during the course of self-treatment was made by 63.8% and 55.6% of students, respectively. At least two kinds of antibiotics were simultaneously taken by 82.6% of students. The majority of self-medicated students failed to complete the course of antibiotics. Adverse reactions were reported by 16.3% of students. Amoxicillin was the most common antibiotic used for self-medication. Conclusions High prevalence of SMA was noted among STU students. Presence of risk factors and risk-associated behaviors/attitudes in the study population calls for focused educational intervention and stricter governmental legislation and regulation of antibiotic use and sale in pharmacies.